ANALISIS SISTEM DAN PROSEDUR PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA BITUNG - Lombok, Donfridel Grafland; Manosso, Hendrik; Afandi, Dhullo (Sam Ratulangi University, 2020)
Rural and Urban Land and Building Taxes is a taxes on land and / or buildings owned, controlled and / or utilized by individuals or entities, except areas that are used for plantation, forestry and mining business activities. The basis for the imposition of land an building tax is tax object sale value. This study aims to analyze the adequacy of the system and procedure for receiving land and building tax in the city of bitung. The method used in the research is qualitative. The results of the research of the System and data collection are in accordance with the current Regulation,wile the payment is not yet appropriate, the internal control analysis system is in compliance. The conclusion of this receart is the system and procedure of registration and data colletion in accordance with the applicable regulation and the payment is not appropriate. BPPRD writers advices things that have ben carried out according to the rules in maintain and implanment a playment system where payment is indicated.